Simple extraction for the scanning of antioxidant activity of vegetables and fruits in Buriram, Thailand by DPPH, ABTS and FRAP assays - Maneetong, Sarunya (Creative Science, 2019)
The simple extraction from 12 plants in Buriram, Thailand were studied on the ethanol solution and the scanning of antioxidant activity by DPPH, ABTS and FRAP assays. The suitable conditions for simple extraction as follow 2 g of dried sample, 30 mL of 75% ethanol at room temperature. The results of antioxidant activity showed that the highest inhibition percentage about 90% were obtained in Spondias pinnata, Schinus terebinthifolius Raddi, Schleichera oleosa (Lour.) Oken. and Ampelocissus arachnoidea (Hassk.) Planch. The inhibition percentage about 60-80% were obtained in Eryngium foetidum L., Mentha cordifolia Opiz., Momordica charantia L., Basella rubra L., Amaranthus viridis L., Ampelocissus martinii Planch. and Polygonum odoratum Lour., respectively. The lowest antioxidant activity was presented in Kaempferia galanga L. (23%) by DPPH and ABTS assays. The antioxidant activities from FRAP assay showed almost the same patterns of activities as the DPPH and ABTS assays.